An integrated approach: fake review detection using convBERT-BiLSTM classification - Mahmud, Md. Anas; Hasan, Alina; Mahbub, Tajrian; Rafi, Navid Hasan; Faiaz, Rushayed Ali (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2024.